Reator de lodos ativados para a produção de bioflocos com efluente da carcinicultura - Carvalho, João Luís de Lima (2017)
The generation of bioflocs for feed in shrimp farming is an alternative to increase the incorporation of nutrients, reduce the use of industrial feed as well as treat the water of the crop. This work, carried out at the Biomass Technology Laboratory, located at Embrapa Agroindústria Tropical, used a activated sludge reactor in bench scale, with prolonged aeration, to produce biofloks from residual water of both nursery and fattening tanks of the marine shrimp Litopenaeus vannamei, available at the Laboratory of Nutrition of Aquatic Organisms (LANOA / UFC). After inoculation with microorganisms from nursery tanks and adaptation of the systems, the reactor was operated for 189 days, with weekly determinations of total suspended solids (TSS), volatile suspended solids (VSS), fixed suspended solids (FSS), chemical oxygen demand (COD) and pH, aiming to produce 5g of VSS in the decanted sludge. Due to periods of anaerobiosis, caused by malfunctioning events of the reactor, the maximum production obtained for VSS was 3.4 g, while the TSS reached 4 g. The efficiency of organic matter removal was 71%. Although anaerobic events had occurred, there was a tendency to produce bioflocs. Even though the treatment of the effluent was not the main objective of the research, the system met National standards, but it needs to be optimized to fit in the State standard. The VSS concentrations did not reach the expected level, but a satisfactory value was obtained when compared to other works of external biofloc production.